Determination of Heavy Elements (Lead, Cadmium, Copper, and Iron) in Samples of Black Tea in the Libyan Market (Tripoli) (Comprehensive Journal of Science, 2026)
Tea is one of the agricultural crop products that are consumed in very large quantities as it has become consumed daily and by different age groups.Due to the increasing trend of manufacturing and using chemicals for the purpose of increasing production, heavy metal pollution has become a source of concern in the food and beverage trade because these metals cause serious health problems for humans because they are not biodegradable and remain in the environment and are transmitted to the food chain. For this reason, this research focused on the most popular types of tea in the Libyan market and measured the concentration of some heavy metals (lead, cadmium, copper and iron) in these types and then compared them with local and international specifications. Samples were collected from a group of different markets in the city of Tripoli during the months of September and October 2023. 10 samples of red tea were collected from different foreign companies.After the digestion process of the samples was carried out using the wet digestion method and using the Flame Atomic Absorption Spectrometry device to measure the concentration of some metals (FAAS) (Flame Absorption Spectrometry) where the results of the study showed that the concentration of cadmium, copper and iron for all measured samples were within the permissible limits and in compliance with the Libyan standard specifications as well as the standard specifications International and European Union and the Codex Alimentarius Commission CODEX While the concentration of lead in some samples exceeded the permissible limit according to Libyan and international specifications by small percentages. In this regard, the values of lead concentrations ranged between (0.01- 6.885 mg/kg), cadmium values ranged between (0.01-0.009 mg/kg), copper values ranged between (0.01 - 6.731 mg/kg) while iron values ranged between (50.36 -140.71 mg/kg) .
Keywords: Cadmium, Lead, Copper, Iron, Tea and Flame Atomic Absorption Spectroscopy (FAAS).